2012
DOI: 10.1258/ar.2012.120015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidental focal hypermetabolic uptake in the breast as detected by 18F-FDG PET/CT: clinical significance and differential diagnosis

Abstract: Incidental focal 18F-FDG uptake in the breast as detected by PET/CT was indicative of malignancy in 45% of patients. Both mean SUV(max) and diameter were greater for malignant than benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
6
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 14 publications
5
31
6
4
Order By: Relevance
“…The former reflects the lower incidence of breast cancer in Korea (25), and the latter may be related to subjective visual assessment by the three nuclear medicine physicians. The malignancy rate in the current study was lower than that in other reports (37.5-83.3%) (16)(17)(18)(19)(20). This might be due to a higher proportion of excluded patients (23.3 vs. 0-9.0%) who underwent no histologic confirmation or insufficient follow-up.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The former reflects the lower incidence of breast cancer in Korea (25), and the latter may be related to subjective visual assessment by the three nuclear medicine physicians. The malignancy rate in the current study was lower than that in other reports (37.5-83.3%) (16)(17)(18)(19)(20). This might be due to a higher proportion of excluded patients (23.3 vs. 0-9.0%) who underwent no histologic confirmation or insufficient follow-up.…”
Section: Discussioncontrasting
confidence: 87%
“…The incidence of incidental hypermetabolic lesions in the current study was lower than that of the Western population (0.8-1.1%) but higher than that of the Korean population (0.4%) (16)(17)(18)(19)(20). The former reflects the lower incidence of breast cancer in Korea (25), and the latter may be related to subjective visual assessment by the three nuclear medicine physicians.…”
Section: Discussioncontrasting
confidence: 55%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Results on the prevalence of BIU and their malignancy rate in the most important studies and in the present are summarised in Table 1 The nodule at CT was 20 mm of diameter, SUV max was 2.7, BIU to liver ratio was 0.9 and BIU to blood-pool ratio was 0.5. After biopsy the final diagnosis was fibroadenoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kang et al 15 13,897 female patients who underwent 18 F-FDG-PET/CT for non-breast malignancies were retrospectively evaluated; fifty women had BIU but two patients were lost to follow-up; 18 (37.5%) had confirmed malignancy while 30 (62.5%) had benign lesions. Chae et al 16 observed 131 BIU in 32,988 patients; seventy-one patients underwent further investigations 32 of which had histologically malignant lesions and 28 benign ones. Breast lesions in the remaining 11 patients, who showed no further evidence of breast malignancy over at least 2-years follow-up, were considered to be clinically benign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation